(untitled) (Patan Pragya, 2020)
The study primarily looks upon the areas of skills and expertise of elderly and their ability to generate employment based on their own experiences. The study was done in Mandandeupur Municipality of Kavre, where 106 elderly were interviewed regarding their knowledge and experiences, skill transfer and its benefits for younger generation. The study also examines the current status of elderly in the society as well as their economic contribution in their families. Conducted in a rural location; almost all of the elderly were involved in agriculture as their main profession and had started their line of profession without any prior trainings of any sort. This further shows the need of initiating programs via government to link older people with younger generation for skill transfer and innovations in traditional farming system as they still see the relevancy of their profession in the coming ten years. Although the younger generation is shifting towards modernization and glamorous professions rather than agriculture, older people still believe that embracing their line of work can improve younger generations’ social status and generate adequate revenue. It is evident that their traditional skills are currently capable of contributing to their economy so combining that with modern techniques can contribute to better income and employment generation as well.